The Association between D-dimer Concentration and Laboratory Parameters for Plasma Leakage in Dengue Infection - Suhendro Suwarto; Riyanti Astrid Diahtantri; Elian Hudiya (Jurnal Penyakit Dalam Indonesia)
Introduction. Plasma leakage and activation of the coagulation system are the pathological hallmark of dengue hemorrhagic fever (DHF) that causes an increase in D-dimer concentration due to the degradation of fibrin clots. This study was conducted to determine the association between of D-dimer and laboratory parameters of plasma leakage, namely: thrombocytopenia, hypoalbuminemia, hemoconcentration and concentration of serum glutamic oxaloacetic transaminase (SGOT) in dengue infected patients.